Peut-on élaborer une approche ergonomique du « temps long » ? - Willy Buchmann; Céline Mardon; Serge Volkoff; Corinne Archambault (Perspectives Interdisciplinaires sur le Travail et la Santé)
This article looks at the possibility of integrating long-term dimensions into ergonomics, which could be done by combining the ergonomics approach, occupational medicine, and demographic analysis. Work-related musculoskeletal disorders represent the common thread of this article.After presenting the theoretical framework, which focuses on long-term approaches to studying the relation between health and work, we concentrate on the methods used and how they complement each other to achieve better results. We then take another look at the main results, which belong to three kinds of processes (adjustments, wear and tear, and selection).Above and beyond this study, we question the capacity of ergonomics to create and develop analysis methods that extend beyond the short-term temporal framework. In so doing, we suggest that ergonomics go one step further and take on a new role in a larger model of the relation between health and work.